Examining knowledge transfer activities in UK universities: advocating a PROMETHEE-based approach. Issue 6 (30th July 2020) - Ishizaka, Alessio; Pickernell, David; Huang, Shuangfa; Senyard, Julienne Marie
Abstract : Purpose: The purpose of this study is to examine the portfolio of knowledge transfer (KT) activities in 162 UK higher education institutions. In doing so, this study creates an index and ranking, but more importantly, it identifies specific groupings or strategic profiles of universities defined by different combinations and strengths of the individual KT activities from which the overall rankings are derived. Previous research, concentrating on entrepreneurial universities, shows that individual knowledge transfer (KT) activities vary substantially among UK universities. The broad portfolio of universities' KT activities, however, remains underexplored, creating gaps in terms of the relative strength, range, focus and combination of these activities, and the degree to which there are distinct university strategic KT profiles. By examining KT activities and grouping universities into KT "types", this research allows universities and policymakers to better develop and measure clearer KT-strategies. Design/methodology/approach: The present study applied the Preference Ranking Organization Method for the Enrichment of Evaluations (PROMETHEE) to rank universities based on their portfolio of KT activities. It utilised data from the 2015–2016 Higher Education Business and Community Interaction Survey dataset. Findings: Findings show that universities differ substantially in their portfolios of KT activities. By using PROMETHEE, a new ranking of universities is generated, based on their KT portfolio. This paper also identifies four distinct types or groups of universities based on the diversity and intensity of their KT activities: Ambidextrous, broad, focused and indifferent. Originality/value: The study contributes to the entrepreneurship literature, and more specifically entrepreneurial activities of universities through new knowledge generated concerning university KT activity. The research extends the existing literature on university archetypes (including those concerned with the Entrepreneurial University) and rankings using a new technique that allows for more detailed analysis of the range of university KT activities. By applying the PROMETHEE approach, results illustrate a more nuanced definition of university KT activities than before, by simultaneously evaluating their overall strength, range, focus and combination, allowing us to identify the universities' strategic profiles based on their KT portfolios. Implications of the findings for key stakeholders include a potential need for government higher education policymakers to take into account the different mixes of university archetypes in a region when considering how best to support higher education and its role in direct and indirect entrepreneurship promotion through regional policy goals.